UPAYA MAHASISWA INSTITUT AGAMA ISLAM AL-ZAYTUN INDONESIA DALAM MEMENUHI KEBUTUHAN FINANSIAL SELAMA MASA STUDI - Mulfi Insani; Sobirin, Muhammad Nur Kholis Abdurrazaq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the efforts and motivations of students at Institut Agama Islam Al-Zaytun Indonesia (IAI AL-AZIS) in generating additional income during their studies to support financial needs and Mandatory Student Contributions (SWM). A descriptive qualitative approach was employed with data collected through interviews, observations, and documentation of six selected students. Findings reveal engagement in small businesses, campus work, and digital platforms. Motivation analysis based on Maslow’s Hierarchy of Needs and Self-Determination Theory (SDT) includes physiological, safety, social, esteem, and self-actualization needs. Economic activities contribute to character development and independence. Recommendations include enhanced campus support via scholarships, entrepreneurship training, and mentoring.